Emergency management and urban resilience under seismic risks. Part I: Theoretical approach for quick post-quake damage evaluation of buildings - Ahmed Mebarki; Sandra Jerez; Mehdi Boukri; Benazouz Chikh; Abdellatif Benbokhari (Emergency Management Science and Technology)
This paper addresses topics related to emergency management and urban resilience under seismic risk. It focuses on post-seismic structural damage evaluation and urban resilience: the damage suffered by buildings influence the residual capacity for dwelling and sheltering at early post-disaster stages. This paper proposes a new theoretical method for quick evaluation of these damages: it derives the global structural damage from the observed damage on the structural components of a frame, i.e. beams and columns (vertical components, horizontal, or bracing elements). The global residual capacity of the building is derived from those of the successive stories: from the basement to the roof. Therefore, it proposes a relationship between the structural damage and the residual probability of failure. It also develops and assigns adequate importance factors for each component (beam, column), at the story level, and importance factor for each story and its location, from bottom to top. The proposed method is compared with classical mechanical approaches: the global damage values are in good accordance, for the adopted case studies. Furthermore, a pushover analysis is performed in order to investigate the influence of the columns' location at the story level: the column's influence it located at the edge, interior, or exterior location. The investigation of the effect of the column location in a story, of the story location along the building height, will contribute in developing new quick evaluation forms at the post-seismic stage and allow quick recovery at the urban scale.